Comparison between different neoadjuvant chemotherapy regimens and local therapy alone for bladder cancer: a systematic review and network meta-analysis of oncologic outcomes - Aydh, Abdulmajeed; Sari Motlagh, Reza; Alamri, Abdulaziz; Yanagisawa, Takafumi; Ayed, Adil; Rajwa, Pawel; Laukhtina, Ekaterina; Alasiri, Saeed M; Kawada, Tatsushi; Mostafai, Hadi; Ayidh, Abdulelah; Pallauf, Maximilian; et al. (World journal of urology, 2023)
PURPOSE: The present systematic review and network meta-analysis (NMA) compared the current different neoadjuvant chemotherapy (NAC) regimes for bladder cancer patients to rank them. METHODS: We used the Bayesian approach in NMA of six different therapy regimens cisplatin, cisplatin/doxorubicin, (gemcitabine/cisplatin) GC, cisplatin/methotrexate, methotrexate, cisplatin, and vinblastine (MCV) and (MVAC) compared to locoregional treatment. RESULTS: Fifteen studies comprised 4276 patients who met the eligibility criteria. Six different regimes were not significantly associated with a lower likelihood of overall mortality rate compared to local treatment alone. In progression-free survival (PFS) rates, cisplatin, GC, cisplatin/methotrexate, MCV and MVAC were not significantly associated with a higher likelihood of PFS rate compared to locoregional treatment alone. In local control outcome, MCV, MVAC, GC and cisplatin/methotrexate were not significantly associated with a higher likelihood of local control rate versus locoregional treatment alone. Nevertheless, based on the analyses of the treatment ranking according to SUCRA, it was highly likely that MVAC with high certainty of results appeared as the most effective approach in terms of mortality, PFS and local control rates. GC and cisplatin/doxorubicin with low certainty of results was found to be the best second options. CONCLUSION: No significant differences were observed in mortality, progression-free survival and local control rates before and after adjusting the type of definitive treatment in any of the six study arms. However, MVAC was found to be the most effective regimen with high certainty, while cisplatin alone and cisplatin/methotrexate should not be recommended as a neoadjuvant chemotherapy regime.
Keywords: doxorubicin; Humans; cisplatina; protokoly protinádorové kombinované chemoterapie; Cisplatin; Antineoplastic Combined Chemotherapy Protocols; Neoadjuvant Therapy; nádory močového měchýře; Methotrexate; Vinblastine; síťová metaanalýza; methotrexát; Gemcitabine; neoadjuvantní terapie; vinblastin; Network Meta-Analysis as Topic; Urinary Bladder Neoplasms; Bayes Theorem; lidé; Cystectomy; cystektomie; Doxorubicin; gemcitabin; Bayesova věta